Performance Performance Evaluation of TLS II CC 07 and CC 08 Load-out in July 2022 at PT. Bukit Asam Tbk, Tanjung Enim, South Sumatra : Evaltuation Perfomance - Abbil Raihan, Muhammad; Adree Octova (EarthCare, 2024)
Coal is one of the fuels sourced from solid hydrocarbons. Bataubara itself is formed from plants and microorganism that solidifies due to the influence of pressure. The use of coal as a fuel is widely used in large industries, such as the cement industry and in steam power plants. administratively the mining concession of PT. Bukit Asam, Tbk. is included in the Tanjung Enim City, South Sumatra Province. In July 2022, there was a torn Coal Conveyor-07 (CC-07) incident that disrupted productivity at TLS 2 (Train Loading Station) so that it could not deliver coal, causing losses to the company with a total of 42,562 tons. With a total loss of Rp. 28,372,329,681.